Regional variation in climate change alters the range-wide distribution of colour polymorphism in a wild bird - Koskenpato Katja; Lehikoinen Aleksi; Morosinotto Chiara; Gunko Ruslan; Karell Patrik (WILEY, 2025)
According to Gloger's rule, animal colouration is expected to be darker in wetter and warmer climates. Such environmental clines are predicted to occur in colour polymorphic species and to be shaped by selection if colour morphs represent adaptations to different environments. We studied if the distribution of the colour polymorphic tawny owl (Strix aluco) morphs (a pheomelanic brown and a pale grey) across Europe follow the predictions of Gloger's rule and if there is a temporal change in the geographical patterns corresponding to regional variations in climate change. We used data on tawny owl museum skin specimen collections. First, we investigated long-term spatiotemporal variation in the probability of observing the colour morphs in different climate zones. Second, we studied if the probability of observing the colour morphs was associated with general climatic conditions. Third, we studied if weather fluctuations prior to the finding year of an owl explain colour morph in each climate zone. The brown tawny owl morph was historically more common than the grey morph in every studied climate zone. Over time, the brown morph has become rarer in the temperate and Mediterranean zone, whereas it has first become rarer but then again more common in the boreal zone. Based on general climatic conditions, winter and summer temperatures were positively and negatively associated with the proportion of brown morph, respectively. Winter precipitation was negatively associated with the proportion of brown morph. The effects of 5-year means of weather on the probability to observe a brown morph differed between climate zones, indicating region-dependent effect of climate change and weather on tawny owl colouration. To conclude, tawny owl colouration does not explicitly follow Gloger's rule, implying a time and space-dependent complex system shaped by many factors. We provide novel insights into how the geographic distribution of pheomelanin-based colour polymorphism is changing.